Prosedur Alih Media Arsip Menggunakan Metode Konversi pada Dinas Kependudukan dan Pencatatan Sipil Kota Malang - Theo Vanda Estapa Rangga; Fahmi Muhammad Az Zuhri (INDO PUBLISHING, 2026)
This study examines the media conversion procedure for birth certificates at the Department of Population and Civil Registration in Malang City. Its goals are to preserve archival information, simplify retrieval, and establish a relevant policy. Using an action research method, data was collected through questionnaires and interviews, then analyzed in two cycles with a Likert scale. The main result is a Standard Operating Procedure (SOP) for media conversion of birth certificate archives. This SOP acts as a work guide for technical staff, filling a gap since the agency previously had no standard procedure. Although the study's findings have not been formally approved by the department head, their validity is considered strong because they have been approved by the division head.